Efeito do condicionamento ácido seletivo e da condição do esmalte decíduo na união de um sistema adesivo universal - Antoniazzi, Bruna Feltrin (2015)
Universal adhesive systems were developed with the purpose of being used both in self-etching or acid-etching strategy. Laboratory studies to test the bond strength of these adhesive systems under different conditions of the substrate are essential to predict their clinical behavior. Thus, the aim of this study was to compare the bond strength of Scotchbond Universal Adhesive system in both strategies (SBU-ER and SBU-SE) with a two-step self-etch adhesive system - Clearfil SE Bond (CSE) to enamel of sound and demineralized primary teeth. 36 primary molars was selected and allocated into 6 groups (n=6). The buccal and lingual sections were ground and the group of demineralized teeth was submitted to pH cycling. The adhesive protocol was performed according to manufacturers' instructions. The methodology used to evaluate the bond strength was the microshear and data were obtained in MPa. After Kolmogorov-Smirnov normality test, the results were submitted to ANOVA and Tukey test (α = 0.05). The SBU adhesive system in the ER mode presented bond strength values (16.57 ± 6.55) statistically higher than SBU-SE (10.79 ± 4.75) and the CSE system (12.62 ± 5.42) and the last two were statistically similar. Substrate condition influenced the bond strength values, and the demineralized enamel (9.22 ± 4.07) were statistically lower than sound enamel (17.44 ± 4.07). It was concluded that the use of acid conditioning prior to the application of universal adhesive system tested improve bond strength values to primary teeth enamel. In addition, enamel demineralized negatively influences the performance of tested adhesive systems.